Prospects for food production and consumption in developing countries. World agricultural trade and food security - Bale, Malcolm D. (American Economic Review, 1983)
The available evidence indicates that, in aggregate, the growth in world food production over the past two decades has more than kept pace with the growth in population. This paper analyzes recent trends in world food production and consumption and outlines the Bank's approach to projections of food production and consumption providing results to the year 1995. It is shown that levels of consumption of various food items have improved in developing countries and are expected to continue to improve. Moreover, the results indicate favorable prospects for food production in developing countries. The paper comments throughout on areas where further work is required to refine the projection method and qualifies the generally optimistic outlook by identifying the types of actions that will be needed to accelerate food consumption and production in developing countries. Pricing policies in agriculture are seen as being particularly critical to the optimal development of the agricultural system in developing countries. International agricultural trade and food security is a matter of considerable concern to a large share of the world's population. Contradictory views on the subject exist. This paper is organized in three parts: i) a summary of world food trade and the trends that have recently emerged; ii) a discussion of world food security and the costs and benefits of a global food security scheme; and iii) an examination of specific countries' policies toward agriculture and food trade to demonstrate how government intervention can either contribute to or inhibit agricultural trade and food security. The paper concludes that when governments intervene in the legitimate functioning of markets, the ultimate outcome is to reduce national and global welfare since they seldom foresee all the ramifications of their actions.